2020
DOI: 10.17576/jsm-2020-4901-09
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Crystallinity of Zeolite Beta on Physicochemical Properties and Performance of Cobalt Catalysts

Abstract: In the present work, the effect of crystallinity of zeolite beta in a sodium form (NaBEA) on physicochemical properties and performance of NaBEA-supported cobalt catalysts was investigated. The incipient wetness impregnation method was utilized in the synthesis of NaBEA-supported cobalt catalysts with various Co loadings (4, 7 and 10 wt. %). NaBEA materials with high and low crystallinities (NaBEA-H and NaBEA-L) were synthesized using fumed silica with aging times of 72 and 48 h, respectively. In comparison to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…It indicated that the crystalline structure of the zeolite catalysts upon acid treatment and modification was perfectly fine, and no damage could be justified. This would suggest that the zeolite catalysts would show a good performance (Phatai et al, 2020) in the esterification of the Sengon wood bio-oil.…”
Section: The Characteristics Of the Zeolite Catalystsmentioning
confidence: 99%
“…It indicated that the crystalline structure of the zeolite catalysts upon acid treatment and modification was perfectly fine, and no damage could be justified. This would suggest that the zeolite catalysts would show a good performance (Phatai et al, 2020) in the esterification of the Sengon wood bio-oil.…”
Section: The Characteristics Of the Zeolite Catalystsmentioning
confidence: 99%